2005
DOI: 10.1002/jgm.764
|View full text |Cite
|
Sign up to set email alerts
|

Functional transfer of eukaryotic expression plasmids to mammalian cells by Listeria monocytogenes: a mechanistic approach

Abstract: In this work we demonstrate that low rates of bacteria-mediated transfection are not due to poor invasion of bacteria, insufficient bacterial lysis, or plasmid DNA degradation. Our data suggest that the transferred plasmid DNA is associated with higher macromolecular structures inhibiting nuclear transport and transgene transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Zelmer et al [12] described in details the various crucial parameters involved in plasmid transfer from Listeria monocytogenes to mammalian cells. They concluded that low-rates of bacteria-mediated-transfection is due to plasmid DNA association with higher proteic macromolecular structures inhibiting nuclear transport and thus transgene production.…”
Section: Discussionmentioning
confidence: 99%
“…Zelmer et al [12] described in details the various crucial parameters involved in plasmid transfer from Listeria monocytogenes to mammalian cells. They concluded that low-rates of bacteria-mediated-transfection is due to plasmid DNA association with higher proteic macromolecular structures inhibiting nuclear transport and thus transgene production.…”
Section: Discussionmentioning
confidence: 99%
“…This view was supported by the fact that cytosolic expression of the plasmid was not possible. Bacterial transfer of an IRES-flanked reporter gene controlled by the T7 promoter into a cell that expressed T7 polymerase did not result in reporter gene expression (Zelmer et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Such bacteria were less toxic to the host cells and could consequently be used at higher multiplicities of infection (MOIs) (Krusch et al, 2002). Although transfection efficiencies of up to 30% could be reached with certain cell lines, the requirement of MOIs of over 100 indicated that several obstacles exist for an efficient DNA transfer (Zelmer et al, 2005). We could exclude release of plasmids and their stability within the host cell as limiting factors.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[17][18][19] These studies have mainly focused on transfer of the GFP reporter gene. However, more relevant to our work, recombinant E. coli and L. monocytogenes were recently used to transfer artificial chromosomes carrying the CFTR gene locus 20 or a pCMV-CFTR plasmid, 10,21 respectively, to cell lines in vitro.…”
Section: Bactofection Of Lung Epithelial Cellsmentioning
confidence: 99%